Gas Cyclones and Swirl Tubes Principles, Design and Operation - Hoffmann, Alex C.; Stein, Louis E. (Springer Berlin Heidelberg, 2002)
The subject of this book is centrifugal gas separation devices, namely cyclones used for gas purification, solids collection and for demisting. The optimization of cyclone performance for any given task is an often-sought goal but is seldom achieved in practice. Understanding cyclone performance as a function of a cyclone's size, geometry, feed properties, feed flow rates and the system of which it is a part, is essential if one wishes to successfully design, operate, troubleshoot or predict cyclone performance. The information presented in this expanded book edition will help to develop this understanding